Applicability of pulsed power technique for the degradation of methylene blue. (June 2016) - Singh, Raj Kamal; Babu, Vigneshwar; Philip, Ligy; Ramanujam, Sarathi
Abstract: Present study evaluated the efficiency of pulsed power technique (PPT) for the degradation of methylene blue (MB) under different operating and environmental conditions. Various reactive oxygen species (ROS) such as hydroxyl radicals, hydrogen peroxide, ozone and superoxide radical were quantified. The maximum concentrations generated were found to be 63 mg/L, 28 mg/L, 1 mg/L and 18 mg/L for hydroxyl radicals, hydrogen peroxide, ozone and superoxide radical, respectively for 12 min of pulsed streamer discharge at 23 kV applied voltage and 25 Hz frequency. It was observed that magnitude of applied voltage, frequency (pulses/sec), pH, alkalinity and natural organic matter (NOM) present in the water had a significant effect on hydroxyl radical and hydrogen peroxide generation. MB degradation efficiency and ROS formation increased with applied voltage and frequency. An initial MB concentration of 50 mg/L was completely degraded within 10 min at 23 kV input voltage and 25 Hz frequency. Acidic pH favoured ROS formation whereas high alkalinity and NOM reduced the MB degradation efficiency and ROS formation. Treatment time for the 100% degradation of 10 mg/L of MB was increased from 6 min to 8 min in presence of 150 mg/L of alkalinity. The MB degradation efficiency was further decreased to 95.6% when alkalinity was increased to 300 mg/L for 10 min streamer discharge. Mineralization of dye during treatment was confirmed by total organic carbon and inorganic ions analyses and IR spectra. Energy efficiency of ROS formation in the reactor was also evaluated.